2020
DOI: 10.3390/cancers13010015
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming by Malat1 Depletion in Prostate Cancer

Abstract: The lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) promotes growth and progression in prostate cancer (PCa); however, little is known about its possible impact in PCa metabolism. The aim of this work has been the assessment of the metabolic reprogramming associated with MALAT1 silencing in human PCa cells and in an ex vivo model of organotypic slice cultures (OSCs). Cultured cells and OSCs derived from primary tumors were transfected with MALAT1 specific gapmers. Cell growth and surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 70 publications
0
26
1
Order By: Relevance
“…The role of lncRNAs in tumor development and metabolism have received increasing attention [33].For example, the lncRNA MALAT1, UCA1, NBR2, etc. has been reported to regulate tumor cell metabolism, including promotes a glycolytic phenotype and increased lactate production, through regulating metabolic transcription factor, enzymes and relating pathways [34][35][36]. HIF-1α-stabilizing lncRNA (HISLA) from tumor-associated macrophages regulates aerobic glycolysis in breast cancer cells by inhibiting the hydroxylation and degradation of HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…The role of lncRNAs in tumor development and metabolism have received increasing attention [33].For example, the lncRNA MALAT1, UCA1, NBR2, etc. has been reported to regulate tumor cell metabolism, including promotes a glycolytic phenotype and increased lactate production, through regulating metabolic transcription factor, enzymes and relating pathways [34][35][36]. HIF-1α-stabilizing lncRNA (HISLA) from tumor-associated macrophages regulates aerobic glycolysis in breast cancer cells by inhibiting the hydroxylation and degradation of HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…Docetaxel treatment, on the other hand, may increase the generation of AR-V7 via altering the MALAT1/SF2 complex, potentially causing enzalutamide resistance [50]. Further, targeting MALAT1 was shown to change PCa cell metabolism towards a more glycolytic phenotype and to decrease the expression of oxidative phosphorylation enzymes causing cell arrest and death by Nanni et al [51]. Among others, underlying mechanisms for these effects of MALAT1 in PCa were shown to be upregulation of miR-140 [52], deregulation of miR-1 and KRAS [53], enhancing function of EZH2 [54], as well as association with estrogen receptor subunits on the chromatin level [55].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Malakar et al reported that a metabolic transcription factor, TCF7L2, is stabilized by MALAT1 and mediates the upregulation of glycolytic activity but decreases gluconeogenic enzymes via the mTORC1-4EBP1 axis [ 209 ]. Similarly, Nanni et al showed that MALAT1 silencing reduces the expression of some metabolic enzymes, including malic enzyme 3, pyruvate dehydrogenase kinases 1 and 3 and choline kinase A, which promotes a glycolytic phenotype and increased lactate production [ 210 ]. As we have described in the previous sections, the activation of glycolysis in tumor cells triggers an immunosuppressive tumor microenvironment.…”
Section: Noncoding Rnas Regulate Both Tumor Metabolism and The Immune Microenvironmentmentioning
confidence: 99%